Nursing process applied to a mother gynecobstetric teenager: a case study - Nathalie Alfaro Vargas (Universidad de Costa Rica, 2013)
The present article summarizes the intervention done towards an adolescent mother who had a twin pregnancy. The methodology used is the process of nursing attention; the process is divided into four stages: first, the stage of valuating in which information is gathered through the revision of the health file of the adolescent and the application of the nursing history; the second stage is nursing diagnosis used to identify the problems presented by the patient; the third stage is planning which includes the designing of objectives and actions that would lead the interventions. The previous information is summarized in the "Plan de Cuidados de Enfermería" based on the theory of Dorotea Orem. Finally, it was apply the stage of performing in which there were implemented actions with the adolescent mother; she obtained necessary information based on her needs for the improvement of life quality. Comprehensive and timely intervention allowed the reduction of risks for the mother and her children and the use of Orem's theory allowed the teenager taking skills to cope with their new role as mother.